Kemajuan Teknologi Memiliki Dampak Signifikan terhadap Perkembangan Pendidikan Sekolah Dasar - fu`adah, eva fanny (Maliki Interdisciplinary Journal, 2025)
The development of technology, especially through the internet, digital devices and social media, has had a significant impact on the character education of children in primary schools. On the one hand, technology provides various interactive learning tools and resources that support the education process. However, on the other hand, technological advances also bring their own challenges. Uncontrolled use of technology can disrupt children’s social and emotional development, reduce face-to-face interactions and allow access to inappropriate content. Therefore, it is important for educators and parents to understand how to integrate technology wisely in children’s education. Proper supervision and regulation of technology use can help minimize its negative impact and maximize its benefits in shaping children’s character. A balanced approach to technology use can also strengthen character values such as responsibility, discipline and empathy, and help children prepare to be individuals of good character to face future challenges.